International Law and Sexual Violence in Armed Conflicts - Eboe-Osuji, Chile (International Humanitarian Law Series, 2012)
Sexual violence is a particular brand of evil that women have endured-more than men-during armed conflicts, through the ages. It is a menace that has continued to challenge the conscience of humanity-especially in our times. At the international level, basic laws aimed at preventing it are not in short supply. What is needed is a more conscious determination to enforce existing laws. This book explores ways of doing just that; thereby shoring up international legal protection of women from sexual violence in armed conflicts.